2021
DOI: 10.1037/tra0000989
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Attitudes Related to Trauma-Informed Care Scale (ARTIC).

Abstract: Objective:The purpose of the current study is to validate the Attitudes Related to Trauma-Informed Care Scale (ARTIC; Baker et al., 2016), a measure of trauma-informed care (TIC) attitudes for human service/health providers and educators. Method: The current study with 1,395 human services/health providers and educators from 17 settings examined the factor structure, reliability, and construct validity of the ARTIC. Results: The 7-factor structure of the ARTIC-45 and the 5-factor structure of the ARTIC-35 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
2
49
1
Order By: Relevance
“…Psychometrically robust instruments need to be developed and validated to evaluate, improve, and cause to become widely known TIC. One of the most used instruments is the Attitudes Related to Trauma-Informed Care (ARTIC) Scale, which was developed to evaluate the TIC relevant attitudes of staff working in the settings serving individuals with histories of trauma ( Baker et al, 2016 ; Baker et al, 2021 ). Previous studies confirmed the reliability and the validity of the original version of ARTIC, which has been used increasingly in western countries ( Black et al, 2022 ; Parker et al, 2020 ; Schneider et al, 2022 ).…”
mentioning
confidence: 99%
“…Psychometrically robust instruments need to be developed and validated to evaluate, improve, and cause to become widely known TIC. One of the most used instruments is the Attitudes Related to Trauma-Informed Care (ARTIC) Scale, which was developed to evaluate the TIC relevant attitudes of staff working in the settings serving individuals with histories of trauma ( Baker et al, 2016 ; Baker et al, 2021 ). Previous studies confirmed the reliability and the validity of the original version of ARTIC, which has been used increasingly in western countries ( Black et al, 2022 ; Parker et al, 2020 ; Schneider et al, 2022 ).…”
mentioning
confidence: 99%
“…The Attitudes Related to Trauma-Informed Care (ARTIC; Baker et al, 2016; Baker et al, 2020), a psychometrically validated 45-item measure that assesses respondents’ attitudes toward trauma-informed care, was collected before the first training and after the final training. Respondents provided a nonidentifying personal code at each administration that was used to match pre-and posttest ARTICs.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate more favorable attitudes toward trauma-informed approaches. The ARTIC has demonstrated strong reliability and content validity with educators and service providers (Baker et al, 2016; Baker et al, 2020). Internal consistency reliability in the current sample was excellent (α = .91).…”
Section: Methodsmentioning
confidence: 99%
“…The items were derived from key stakeholder feedback, expert opinions, and scholarly literature (Baker et al, 2016). The new measure has been validated with human health and service providers and school-based staff (Baker et al, 2016(Baker et al, , 2021 and is an efficient and cost-effective measure of attitudes toward trauma-informed care.…”
Section: Pottstown Trauma-informed Community Connection (Pticc)mentioning
confidence: 99%